Antimicrobial Functionalized Mesoporous Silica FDU-12 Loaded with Bacitracin - Vasile, Dan Adrian; Motelica, Ludmila; Mîrț, Luiza-Andreea; Vasilievici, Gabriel; Memecică, Oana-Maria; Oprea, Ovidiu Cristian; Surdu, Vasile Adrian; Trușcă, Roxana Doina; Chircov, Cristina; Vasile, Bogdan Ștefan; Ghizdavet, Zeno Dorian; Ficai, Denisa; et al. (MDPI, 2026)
The threats leading to the extinction of humanity accelerate the evolution and development of materials that are capable of providing conditions for preserving health and, implicitly, life. In our work, we developed drug delivery systems based on mesoporous silica which can deliver an antibiotic, bacitracin, in a more controlled manner. The synthesis of the FDU-12 was performed through a sol–gel method and alternatively functionalized with -NH2 groups or with poly(N-acryloylmorpholine) chains. The loading of bacitracin was performed using the vacuum-assisted method we successfully used to load these mesoporous materials preferentially within the pores as proved by the TGA-DSC results. The release was performed in two types of simulated body fluid (SBF) and this process was evaluated with chromatographic method using UV detection. The obtained data were fitted in three mathematical models of kinetic drug release (Weibull model, Korsmeyer–Peppas model, and nonlinear regression). The antimicrobial evaluation demonstrated that bacitracin-loaded FDU-12 formulations exhibited strong activity against both reference and clinical Staphylococcus strains. At sub-inhibitory concentrations, all formulations significantly reduced microbial adherence and biofilm formation, although certain strain-dependent stimulatory effects were observed. Furthermore, exposure to sub-MIC levels modulated the production of soluble virulence factors (hemolysins, lipase, and amylase), in a formulation- and strain-dependent manner, underscoring the ability of surface-functionalized FDU-12 carriers to influence bacterial pathogenicity while enhancing antimicrobial efficacy.
Keywords: mesoporous silica; poly(N‑acryloylmorpholine); bacitracin; drug delivery; vacuum‑assisted loading; surface functionalization; skin infection; kinetic model; antimicrobial; anti‑biofilm virulence factors modulation; Staphylococcus spp